Outcome study findings of an intensive outpatient program for missionaries and clergy - Jensma, Jeanne L. (Journal of psychology and theology, 2016)
This article reports the findings of an outcome study done at ALONGSIDE, a counseling-focused retreat center that offers three-week intensive outpatient programs for Christian leaders, the majority of whom are missionaries. Repeated measures research utilized the Outcome Questionnaire - 45.2 (OQ-45.2) to explore whether or not clients participating in the three-week intensive outpatient program realized significant clinical progress and whether or not therapeutic gains were retained after the conclusion of the program. Missionaries and other Christian leaders took the inventory online a month before coming to ALONGSIDE, upon arrival, at the end of the three-week program, and three months after the program concluded. The results indicated that a month of time before arrival did not bring about a significant reduction in symptomatology among the 191 subjects, but three weeks of ALONGSIDE's intensive outpatient program resulted in significant clinical improvement which remained when the inventory was taken again three months post-program. This suggests that in a fairly short period of time, an intensive outpatient program consisting of psycho-education, group psychotherapy, and individual and/or marital counseling within a milieu of intentional Christian community can be a highly effective model for promoting enduring psychological healing.